Five Great Sins (Mahāpātakas) with Special Reference to Śaiva Siddhānta - R. Sathyanarayanan (Ksiegarnia Akademicka Publishing, 2021)
The term prāyaścitta covers a number of rites and actions that are held to expiate or repair faults of omission and commission. In fact, many of the expiable offenses that are discussed in Saiddhāntika sources are not exclusively Śaiva but belong also to the realm of smārta traditions for they include such non-criminal and non-transgressive things as states of ritual impurity caused, for example, by life-events such as birth and death. The expiatory procedure for the five great sins vary between Śaiva and smārta systems. Śaiva scriptures prescribe different types of maṇḍalas for these five great sins using five BRAHMA-mantras to expiate along with moon-related fasting of kr̥ cchra, cāndrāyaṇa etc., and initiation (dīkṣā) or an installation of Śiva (pratiṣṭhā). Most of the smr̥ ti nibandhas say that the great sins are not expiable. Here I have focused on these two systems regarding the great sins, mainly taking into consideration the 12th-century Śaiva expiatory manual Prāyaścittasamuccaya of Trilocanaśiva.